A Detailed Overview of the Role of Resveratrol in Feminine Care: Multiple Health Care Benefits - Pal, Rashmi Saxena; Pal, Yogendra; Chaitanya, MVNL; Salahuddin (Current Drug Therapy, 2025)
Resveratrol (RSV) is a polyphenol generated from plants. It is an organic substance that can be found in grapes, some berries, as well as other fruits and nuts. Numerous health benefits, such as anti-proliferative, anti-inflammatory, antidiabetic, anti-ischemic, anti-aging, steroidogenic effects, and antioxidant effects, have been demonstrated for it. Clinical trials show that it is technically safe to take resveratrol in doses up to 5 g per day. Resveratrol has an effect on the most common problems related to pregnancy and has an impact on embryogenesis and the reproductive health of women since it is a phytoestrogen. This paper could serve as a foundation for more in-depth clinical research on various perspectives of resveratrol.
Keywords: phytoestrogen